Age assessment of the bushpig Potamochoerus porcus Linn. 1758 in the southern Cape - Seydack, Armin Hans Wilfried (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--Stellenbosch University, 1983.